Konseling Eklektik Untuk Menurunkan Depresi Pasien Gagal Ginjal Kronis Dengan Hemodialisa di RS X Semarang - . Kasiyati; Rahma Widyana (LPPM Universitas Proklamasi 45, 2022)
Living with End Stage Renal Disease (ESRD) is causing the patients to feel depressed, struggle with problems including physical, psychological, social economy and family. 20-30% of ESRD patients are experiencing depression. Eclectic counseling is one of method to decrease depression. This research aims to understand the effect of eclectic counseling on depression. There were three ESRD patients with depression in Internal Medicine and Hemodialysis Department in X Hospital Semarang. This research was conducted using simgle case pre-experimental design. The data were collected through eclectic counselling module and HRSD (Hamilton Rating Scale for Depression) scale. The data were not normally distributed, thus wilcoxon sign rank testwas chosen as data analysis method. The result showed there were significant difference of depression level in ESRD patients. Depression level were lower after the counseling compared to before counseling. Eclectic counseling has a significant contribution to reduce depression level of ESRD patients on dyalisis in X Hospital Semarang.